A Lattice Boltzmann Modeling Fluid-Structure Interaction Problems and Its Applications in Natural Convections in a Square Cavity with Particles Suspended Inside (Advances in Applied Mathematics and Mechanics, 2018)
Fluid-structure interaction (FSI) occurs in many situations in nature and industries. Traditional descriptions of this problem in computational fluid dynamics (CFD) are mostly at macroscopic level. In this paper, an alternative mesoscopic description, based on lattice Boltzmann method (LBM), is presented for the FSI problems. The FSI are viewed as the collective behaviors of neighboring fictitious particles of the LBM deviating from their equilibrium state when solid boundaries presented in flow. To illustrate the rationality of the present idea, a forced convection over a stationary heated circular cylinder and a circular cylinder with in-line oscillation in fluids are simulated at first and the results are validated by comparing with existing numerical and experimental data in the literatures. For applications, natural convections in a square cavity with maximum three circle particles suspended inside are then carried out and the mechanisms of heat transfer enhancement are investigated. It is found that, adding particles destabilizes the flows in a square cavity and enhances heat transfer.